Respuesta :

Answer

[tex]f(x) = 3x - 5[/tex]

Explain

.

[tex]f(0) = - 5[/tex]

[tex]f(3) = 4[/tex]

.

Find b

[tex]3b - 0b = 4 - ( - 5)[/tex]

[tex]3b = 9[/tex]

[tex]b = \frac{9}{3} \\ [/tex]

[tex]b = 3[/tex]

.

Find f(1)

[tex]f(1) = f(0) + b[/tex]

[tex]f(1) = - 5 + 3[/tex]

[tex]f(1) = - 2[/tex]

.

Find Function

.

[tex]f(x) = f(1) + (x - 1)b[/tex]

[tex]f(x) = - 2 + (x - 1)3[/tex]

[tex]f(x) = - 2 + 3x - 3[/tex]

[tex]f(x) = 3x - 3 - 2[/tex]

[tex]f(x) = 3x - 5[/tex]

[tex] \rm{}fumction \to \boxed{f(x) = 3x - 5}[/tex]

.

#LearnWithBrainly